Protective Effects of Ecklonia stolonifera Extract on Ethanol-Induced Fatty Liver in Rats - Bang, Chae-Young (Biomol Ther (Seoul), 2016)
Chronic alcohol consumption causes alcoholic liver disease, which is associated with the initiation of dysregulated lipid metabolism. Recent evidences suggest that dysregulated cholesterol metabolism plays an important role in the pathogenesis of alcoholic fatty liver disease. Ecklonia stolonifera (ES), a perennial brown marine alga that belongs to the family Laminariaceae, is rich in phlorotannins. Many studies have indicated that ES has extensive pharmacological effects, such as antioxidative, hepatoprotective, and antiinflammatory effects. However, only a few studies have investigated the protective effect of ES in alcoholic fatty liver. Male Sprague-Dawley rats were randomly divided into normal diet (ND) (fed a normal diet for 10 weeks) and ethanol diet (ED) groups. Rats in the ED group were fed a Lieber-DeCarli liquid diet (containing 5% ethanol) for 10 weeks and administered ES extract (50, 100, or 200 mg/kg/day), silymarin (100 mg/kg/day), or no treatment for 4 weeks. Each treatment group comprised of eight rats. The supplementation with ES resulted in decreased serum levels of triglycerides (TGs), total cholesterol, alanine aminotransferase, and aspartate aminotransferase. In addition, there were decreases in hepatic lipid and malondialdehyde levels. Changes in liver histology, as analyzed by Oil Red O staining, showed that the ES treatment suppressed adipogenesis. In addition, the ES treatment increased the expression of fatty acid oxidation-related genes (e.g., PPAR-α and CPT-1) but decreased the expression of SREBP 1, which is a TG synthesis-related gene. These results suggest that ES extract may be useful in preventing fatty acid oxidation and reducing lipogenesis in ethanol-induced fatty liver.